Computational Methods for Application in Industry 4.0 - Karkalos, Nikolaos E.; Markopoulos, Angelos P.; Davim, J. Paulo (Manufacturing and Surface Engineering, 2019)
This book presents computational and statistical methods used by intelligent systems within the concept of Industry 4.0. The methods include among others evolution-based and swarm intelligence-based methods. Each method is explained in its fundamental aspects, while some notable bibliography is provided for further reading. This book describes each methods' principles and compares them. It is intended for researchers who are new in computational and statistical methods but also to experienced users.